Three Collections of Ottoman Manuscripts in Zagreb - Paić-Vukić, Tatjana (2008)
In state institutions in Zagreb, there are three collections of Ottoman, Arabic and Persian manuscripts. The largest one is the Oriental Collection of the Archives of The Croatian Academy of Sciences and Arts, established in 1927. It has two thousand and one hundred Oriental manuscripts mostly acquired from various private libraries in Bosnia nad Hercegovina, Kosovo and Sanjak. It also has about seven hundred and sixty Ottoman documents dating from 1571 to 1916. The vast majority of those materials were collected by two prominent Turkologists of the twentieth century: Franz Babinger and Aleksei Olesnicki. The other two collections are much smaller. The one at the Croatian State Archives belonged to the Austrian nobleman and diplomat, Baron Franz von Ottenfels, and has only a few Ottoman manuscripts. The other, which is kept at the National and University Library, belonged to Mustafa Muhibbi, qadi from Sarajevo who lived in the first half of the nineteenth century.
Projekt MZOS
ENG